2014
DOI: 10.1186/s13065-014-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of chlorogenic acids and related cinnamic acid derivatives from Nicotiana tabacumtissues with the aid of UPLC-QTOF-MS/MS based on the in-source collision-induced dissociation method

Abstract: BackgroundChlorogenic acids (CGAs) are a class of phytochemicals that are formed as esters between different derivatives of cinnamic acid and quinic acid molecules. In plants, accumulation of these compounds has been linked to several physiological responses against various stress factors; however, biochemical synthesis differs from one plant to another. Although structurally simple, the analysis of CGA molecules with modern analytical platforms poses an analytical challenge. The objective of the study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 34 publications
6
111
0
Order By: Relevance
“…2a) and ferulic acid produces ions at m/z 193 [ferulic acid–H] − and m/z 134 [ferulic acid–H–CO 2 –CH 3 ] − (observed also in our study in Fig. 2c) [16, 23, 24]. However, one important observation/evidence emerging from this study is that these diagnostic patterns were only observed when HCA derivatives were attached to quinic acid (Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…2a) and ferulic acid produces ions at m/z 193 [ferulic acid–H] − and m/z 134 [ferulic acid–H–CO 2 –CH 3 ] − (observed also in our study in Fig. 2c) [16, 23, 24]. However, one important observation/evidence emerging from this study is that these diagnostic patterns were only observed when HCA derivatives were attached to quinic acid (Fig.…”
Section: Resultssupporting
confidence: 75%
“…In recent years, liquid chromatography (LC)–MS has become one of the most common techniques for annotation of plant metabolites as well as discerning between different positional isomers of mono -, di - and tri -acyl CGAs [1416, 22, 23, 26, 27]. However, very little has been done for geometrical isomers of CGAs [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compounds 8′ and 9′ showed, besides their pseudomolecular ion, a characteristic fragment at m/z 191 indicating the presence of two 5-O-p-coumaroylquinic acid isomers. Assuming that these two compounds have the same eluting behaviour as previously reported by Ncube et al (2014), compound 8′ was tentatively identified as trans-5-O-pcoumaroylquinic acid and compound 9′ as cis-5-O-pcoumaroylquinic acid.…”
Section: Table 2 -Phenolic Compounds In Schisandra Chinensis Leaves (mentioning
confidence: 88%
“…Compound 6′ Compounds 3′, 4′, 8′, and 9′ ([M-H] − at m/z 338) were assigned to 4-O-p-coumaroylquinic acid, 3-O-p-coumaroylquinic acid, trans-and cis-5-O-p-coumaroylquinic acid, respectively, based on their elution order, fragmentation pattern, and relative abundance (Clifford et al, 2003;Ncube et al, 2014). The fragmentation pattern of compound 3′ was similar to the one previously reported by Clifford et al (2003) for 4-O-p-coumaroylquinic acid by yielding a specific fragment at m/z 174 (according to Clifford et al, 2003:~173.5).…”
Section: Table 2 -Phenolic Compounds In Schisandra Chinensis Leaves (mentioning
confidence: 99%
“…Compound 17 (21.95 min) with molecular ion at m/z 449.0727 was identified as myricetin-arabinoside/xylopyranoside as its MS/MS profile was corresponded with that of the literatures [27]. Compound 18 (23.10 min) was assigned as myricetrin-3-O-rhamnoside (myricitrin) with a [M-H] − ion at m/z 463.0878 and a aglycone ion at m/z 316 [61].…”
Section: Flavonoidsmentioning
confidence: 99%